International Yearbook of Soil Law and Policy 2022 - Ginzky, Harald; De Andrade Corrêa, Fabiano; Dooley, Elizabeth; Heuser, Irene L.; Kameri-Mbote, Patricia; Kibugi, Robert; Ruppel, Oliver C. (International Yearbook of Soil Law and Policy, 2024)
This open access book presents an important discussion on the interface between sustainable soil management and climate mitigation and adaptation. It investigates a variety of aspects in this context, such as the political and societal consequences for countries in the Global South, an assessment of the outcomes of the UNFCCC Conference of Parties held in Glasgow, appropriate legal instruments to promote desealing, regulatory concepts for negative emissions in soil and land use, the debate in Europe on carbon uptake in soils and the climate-related policy of the Convention on Biological Diversity. Lastly, it provides information on recent court rulings on climate mitigation in Germany and Australia and their relevance for sustainable soil management. This sixth volume of the International Yearbook of Soil Law and Policy is divided into four parts, the first of which deals with various aspects of the theme "Climate Mitigation and Adaptation and Sustainable Soil Management." The second part covers recent international developments, the third presents regional and national reports, and the fourth discusses overarching issues. Given the range of key topics covered, the book offers an indispensable tool for all academics, legislators and policymakers working in this field. The "International Yearbook of Soil Law and Policy" series discusses central questions in law and politics with regard to the protection and sustainable management of soil and land - at the international, national, and regional level.